Displacement frames: How residents perceive, explain and respond to un-homing in Black San Francisco. (May 2023) - Loder, Kimya; Stuart, Forrest
Few urban phenomena command as much attention as displacement. Scholars continue to refine conceptualisations of displacement to more effectively capture its diversity in forms, scales and temporalities. Recent research advocates a more inclusive conceptualisation, attuned to the processes of 'un-homing' – that is, the more subtle, 'non-catastrophic' forms of 'slow violence' that rupture residents' phenomenological attachments to place and home. Advocates of the un-homing approach call on researchers to develop the data and analytical frameworks necessary for capturing the perceptions and lived experiences of displacement from the perspective of longtime residents. This article develops one such analytical framework, which we refer to as displacement frames. Building on the conceptual tools of cultural sociology, displacement frames are the evaluative schema through which residents make sense of, and act towards, the slow violence and micro-events of un-homing. Drawing on 32 interviews with long-time Black residents in San Francisco's rapidly gentrifying Bayview Hunters Point neighbourhood, we identify three primary displacement frames: (1) displacement-by-design, (2) displacement-as-predation and (3) displacing-the-problem. As a product of residents' historical experiences, networks and housing tenure, these frames simplify complex (and often ambiguous) experiences into a coherent narrative about the primary causes, conditions and consequences of displacement. In turn, displacement frames influence how and to what extent residents attempt to resist, prevent or perhaps even accept and support local displacement.